Pengaruh Kontribusi Wanita, Green Accounting, dan Ukuran Perusahaan Dalam Meningkatkan Nilai Perusahaan - Kezia Agina Bangun; Thia Margaretha Tarigan (Journal of Business and Economics Research (JBE), 2026)
This study examines the effect of women’s contribution, green accounting, and firm size on firm value in infrastructure companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Focuses on infrastructure companies because the sector plays a strategic role in Indonesia's economic development. The sample was selected through purposive sampling and secondary data from infrastructure companies with consistently available annual reports and audited financial statements during the observation period. By using a quantitative approach method. The results indicate that women directors do not affect firm value (p = 0,278). Indicated the female board representation is not yet a major consideration for investors. Women commissioners has a positive effect on firm value (p < 0,000). Their presence strengthens supervision and corporate governance. Green accounting do not affect firm value (p = 0,709). ISO 14001 certification ownership is insufficient to influence investor decisions, as investors place greater emphasis on financial performance indicators. Firm size has a positive effect on firm value (p = 0,006). The large companies are perceived as more stable and financially capable. These findings support signaling theory, which suggests that corporate information influences investor assessment and firm value. The contribution of this research lies in providing empirical evidence on the effects of women's participation, represented by women directors and women commissioners, green accounting, and firm size on firm value in Indonesia's infrastructure sector. Furthermore, the findings offer practical implications for corporate management in enhancing corporate governance quality and sustainability practices to support firm value creation.